Uncovering The Psychosocial Challenges of Families Caring for Children With Cerebral Palsy: An Aggregated Meta-Synthesis - Andromeda, Andromeda; Hartini, Nurul; Suryanto, Suryanto (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
There is a paucity of literature reviews that highlight the challenges of caring for a child with CP from the family perspective. This study aims to uncover the psychosocial challenges of caring for a child with CP, using the family as a systems approach and synthesising them from the perspectives of parents, siblings and other family members. Using an aggregated meta-synthesis approach, this review included 12 qualitative research articles, which were quality assessed using the Critical Appraisals Skills Programme checklist form for qualitative studies. Based on the synthesis and thematic analysis of the data, four themes of psychosocial challenges in families caring for a child with CP were identified: (1) parents' perspective: coming to terms with the reality; (2) siblings' perspective: a strong and unifying sense of 'us'; (3) other family members' perspective: accepting the caring role; and (4) family unit perspective: maintaining a balanced family system. Each theme has interesting sub-themes that can be explored to improve public knowledge and awareness of disability, in line with intervention programmes for families caring for children with CP.